2008
DOI: 10.1016/j.tet.2007.10.090
|View full text |Cite
|
Sign up to set email alerts
|

New tetracyclic heteroaromatic compounds based on dehydroamino acids: photophysical and electrochemical studies of interaction with DNA

Abstract: A benzothienoindole (BTIN) and a benzofuroindole (BFIN) were synthesized in high yields, as potential new DNA target compounds, using a metal-assisted intramolecular CeN cyclization of the methyl esters of N-(tert-butoxycarbonyl)-b,b-bis(dibenzothien-4-yl or dibenzofur-4-yl)dehydroalanines. The latter were obtained by a bis-Suzuki coupling of a b,b-dibromodehydroalanine with the corresponding heteroarylboronic acids. The absorption and fluorescence properties of the new tetracyclic compounds were studied in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
4
17
0
Order By: Relevance
“…In similar to earlier studies [12,15,17,18,36,37] presenting electrochemical detection of DNA damage induced by several compounds/agents, or by g-radiation, a decrease at the magnitude of guanine signal was similarly observed in our study after in vitro and in vivo interaction of KA with ctdsDNA and genomic DNA in the solution phase. This decrease at the guanine signal can be attributed to the induction of oxidative DNA damage basically on guanine bases, that was also similarly explained for other DNA interactions [17,38].…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In similar to earlier studies [12,15,17,18,36,37] presenting electrochemical detection of DNA damage induced by several compounds/agents, or by g-radiation, a decrease at the magnitude of guanine signal was similarly observed in our study after in vitro and in vivo interaction of KA with ctdsDNA and genomic DNA in the solution phase. This decrease at the guanine signal can be attributed to the induction of oxidative DNA damage basically on guanine bases, that was also similarly explained for other DNA interactions [17,38].…”
supporting
confidence: 91%
“…The pretreated PGEs were immersed into the vials containing either 110 mL of samples containing DNA, or KA incubated DNA. The electrodes were then kept in these vials during 7.5 min followed by passive adsorption procedure [12,14,36]. The PGEs were washed with ABS for 10 s.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these compounds were shown to be DNA intercalators, using absorption and fluorescence techniques [18]. More recently, heteroaryl and heteroannulated indoles [16][17][18][19] and a benzothieno [3,2-b]pyrrole [17] were incorporated in lipid bilayers of phospholipid components of biological membranes (DPPC, DOPE and Egg-PC). Fluorescence anisotropy measurements indicated that they were located in the lipid bilayer, feeling the differences between the gel and the liquidcrystalline phases.…”
Section: Introductionmentioning
confidence: 99%
“…Organic dyes are stabilized on groove by binding and intercalation with DNA through a series of associative interactions such as hydrogen bond, attractive van der Waals, hydrophobic interaction and so on [3]. The intercalative binding is stronger than other two binding modes because the surface of intercalative molecule is inserted into base pairs of DNA.…”
Section: Introductionmentioning
confidence: 99%